From clusters to smart specialization: tourism in institution-sensitive regional development policies - Benner, Maximilian (Economies, 2017)
In the European Union and its neighborhood, regional development has increasingly come to focus on agglomerations during the last three decades. Notably, during the 1990s and early 2000s, clustering was the major policy focus in regional development. Currently, the concept of smart specialization is applied all over the European Union and is attracting interest in the EU’s neighborhood. The tourism sector particularly tends to agglomerate regionally and even locally. While there is a large body of literature describing tourism clusters and while tourism features as a priority sector in many regional development strategies such as smart specialization strategies, there is a research gap on policy approaches applying agglomeration-oriented policy concepts to tourism destinations in an institution-sensitive way. This article argues that both cluster policy and smart specialization can be of considerable value for institution-sensitive tourism development, either when adapted to the specificities of the tourism sector or when integrating tourism development into wider, cross-sectoral strategies of regional development. Such a policy can be a valuable tool for local and regional development, provided that policies are designed in an institution-sensitive manner and respond to the particular institutional context prevailing in a tourist destination. The article illustrates some preliminary thoughts for institution-sensitive tourism development through cluster policy and smart specialization in Cyprus, Israel, and Tunisia.
Keywords: Aufsatz in Zeitschrift